Interviewing media workers - Graf, Heike (MedieKultur: Journal of media and communication research, 2010)
The focus of this article is on the use of Niklas Luhmann’s systems theoretical approach in order to analyse interviews conducted with media workers concerning their experiences of ethnic diversity in newsrooms. Applying systems theory means constructing the interview as a social system and seeing the “data” as observations produced by the observer and not as representations of a reality. The first part of the article describes the interview methodology and the second part provides examples, from the current study, of how systems theory can be applied in order to analyse interviews. Using a difference-theoretical approach means looking at the distinctions the informants make when talking about their experiences. These main guiding distinctions can be summarised as immigrant background/competence as well as advantage/competence. Using the guiding distinction of inclusion/exclusion when interpreting the interviewees’ statements, the interdependencies of mechanisms of inclusion and exclusion in newsrooms related to ethnic background can be examined.